1990
DOI: 10.1177/019874299001500301
|View full text |Cite
|
Sign up to set email alerts
|

Social Maladjustment: An Interpretation

Abstract: The exclusionary term social maladjustment in the definition of serious emotional disturbance, used for Public Law 94–142, has been an enigma for special education. This article is an attempt to make a reasonable and limited interpretation of social maladjustment. It is important that the interpretation of this term be limited because there is a growing effort to interpret social maladjustment in a very broad way to include all disorders of social behavior. The recent Honig v. Doe (1988) decision appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…This clause stipulates that students are not eligible for special education services if they are determined to be “socially maladjusted” and do not also meet criteria for ED. Although this clause has been criticized for being ambiguous and confusing (Center, 1990; Constenbader & Buntaine, 1999; Merrell & Walker, 2004; R. Skiba, Grizzle, & Minke, 1994), it has remained in each new reauthorization of IDEIA (most recent, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This clause stipulates that students are not eligible for special education services if they are determined to be “socially maladjusted” and do not also meet criteria for ED. Although this clause has been criticized for being ambiguous and confusing (Center, 1990; Constenbader & Buntaine, 1999; Merrell & Walker, 2004; R. Skiba, Grizzle, & Minke, 1994), it has remained in each new reauthorization of IDEIA (most recent, 2004).…”
mentioning
confidence: 99%
“…In 1975, when the EHA was developed, the term social maladjustment was described in the Diagnostic and Statistical Manual of Mental Disorders (2nd ed. [ DSM-II ]; American Psychiatric Association [APA], 1968) as a cultural conflict resulting from problems adjusting or adapting to another cultural standard or norm (Center, 1990; Freedman, Kaplan, & Sadock, 1976). This description is a departure from current themes and is no longer a part of the current DSM (4th ed., text rev.…”
mentioning
confidence: 99%
“…Socially maladjusted is not defined in the federal definition, and we are not aware of any information from the U.S. Department of Education that would help differentiate socially maladjusted from ED. Some authorities have offered definitions of the term but none is widely accepted (see Center, 1990; Forness, Kavale, & Lopez, 1993; Kauffman & Landrum, 2009; Wood et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation of SM and ED embroils controversial policy debates about whether the public school system or juvenile justice system should be responsible for treating and ultimately rehabilitating students with conduct problems and antisocial behaviors. Advocating for a restrictive interpretation of ED eligibility, some scholars have suggested that SM reflects social problems such as drug or alcohol use and other risky behaviors or that SM indicates socialized delinquency as in gang involvement or other associations with antisocial peer groups (Center, 1990;Clarizio, 1987;Quay, 1987;Weinberg & Weinberg, 1990). Scholars from this perspective suggest that juvenile delinquency negates schools' responsibility to students' special education needs.…”
Section: Policy Debatementioning
confidence: 99%